Women's health in Canada : critical perspectives on theory and policy - Morrow, Marina Helen, 1963-; Hankivsky, Olena; Varcoe, Colleen, 1952- (Toronto ; Buffalo ; London : University of Toronto Press, 2007)
In recent years, healthcare professionals have recognized the distinctly different healthcare needs and concerns of men and women. Women's health, in particular, has come into its own in the last two decades. In Canada, however, there has been little available in the way of a general text on women's health. This volume works toward filling that gap by providing a resource for teaching and understanding women's health in this country. To lay out the methodological and theoretical foundations for their study, editors Olena Hankivisky, Marina Morrow, and Colleen Varcoe bring together an interdisciplinary group of scholars and practitioners from economics, anthropology, sociology, nursing, political studies, women's studies, and psychology. Contributors draw on the rich history of the Canadian women's health movement, providing analysis of that history and of the emergent theory, policy, and practice. Aimed at undergraduate and graduate students as well as practitioners, the collection adopts an intersectional approach, looking closely at social factors such as gender, race, ethnicity, class, sexuality, and gender identity, and analysing how they relate both to each other and to women's health. Connections between the social, economic, and cultural contexts of women's lives and their physical, spiritual, and mental well-being are a primary focus. Providing a much needed resource for teachers, students, and practitioners of women's health in Canada, this comprehensive volume makes an important contribution to the literature.
Part 4. Key issues in women's health -- 12. Women, drug regulation, and maternal/state conflicts / Susan C. Boyd -- 13. Women's voices matter : creating women-centred mental health policy / Marina Morrow -- 14. Between visibility and vulnerability : women and HIV/AIDS / Meredith Raimondo -- 15. Breast cancer : lived experience and feminist action / Sue Wilkinson -- 16. Selling 'the change' : a comparison of the dangers of hormone replacement therapies in profit versus National Health Care delivery systems / Brian Richter and Cindy Patton -- 17. Women's health and cardiovascular care : a persistent divide / Lynn E. Young -- 18. From global to local and over the rainbow : violence against women / Olena Hankivsky and Colleen Varcoe -- 19. Women's access to maternity services in Canada : historical developments and contemporary challenges / Cecilia Benoit, Dena Carroll, and Rachel Westfall -- 20. Relocating care : home care in Ontario / Pat Armstrong -- Contributors.
Includes bibliographical references.
Print version record.
English.
JSTOR
Keywords: Börngen, ...; Women -- Health and hygiene -- Canada; Women's health services -- Canada; Medical policy -- Canada; Women -- Health and hygiene -- Sociological aspects; Women -- Health and hygiene; Women's health services; Medical policy; Women's Health; Women's Health Services; Health Policy; Canada; Femmes -- Santé et hygiène -- Canada; Femmes -- Services de santé -- Canada; Politique sanitaire -- Canada; Femmes -- Santé et hygiène -- Aspect sociologique; Femmes -- Santé et hygiène.; Femmes -- Services de santé.; Politique sanitaire; SOCIAL SCIENCE -- Gender Studies; HEALTH & FITNESS -- Healthy Living; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Preventive Medicine; Medical policy; Women -- Health and hygiene; Women -- Health and hygiene -- Sociological aspects; Women's health services; Canada; Kanada; Gesundheitspolitik; Frau